Mode identification from spectroscopy of gravity-mode pulsators. Issue Volume 9:Issue S301(2013) (18th February 2014) - Pollard, K. R.; Brunsden, E.; Cottrell, P. L.; Davie, M.; Greenwood, A.; Wright, D. J.; De Cat, P.
Abstract: The gravity modes present in γ Doradus stars probe the deep stellar interiors and are thus of particular interest in asteroseismology. For theMUSICIAN programme at the University of Canterbury, we obtain extensive high-resolution echelle spectra of γ Dor stars from the Mt John University Observatory in New Zealand. We analyze these to obtain the pulsational frequencies and identify these with the multiple pulsational modes excited in the star. A summary of recent results from our spectroscopic mode-identification programme is given.